2011
DOI: 10.1002/ejoc.201001643
|View full text |Cite
|
Sign up to set email alerts
|

L‐Phe‐D‐Oxd: A Privileged Scaffold for the Formation of Supramolecular Materials

Abstract: Some compounds containing the L‐Phe‐D‐Oxd [L‐Phe = L‐phenylalanine; D‐Oxd = (4R,5S)‐4‐carboxy‐5‐methyl oxazolidin‐2‐one] moiety have been prepared and their properties as supramolecular material have been determined. Some derivatives of the dipeptide L‐Phe‐L‐Phe (which usually forms nanotubes) and some long‐chain derivatives that behave as low‐molecular‐weight gelators have been prepared. We have also replaced the D‐Oxd moiety with a D‐Pro (D‐Pro = D‐proline) moiety to check if the presence of the Oxd moiety w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…The synthesis of these molecules has been previously described and may be easily obtained on a multigram scale. 24 The study on the self-assembly capability of molecules 1 and 2 showed that while molecule 2 does not form a gel at any concentration, molecule 1 forms a gel at 10 mM concentration and a highly viscous sol at 5 mM concentration ( Fig. 2A, B).…”
Section: Resultsmentioning
confidence: 97%
“…The synthesis of these molecules has been previously described and may be easily obtained on a multigram scale. 24 The study on the self-assembly capability of molecules 1 and 2 showed that while molecule 2 does not form a gel at any concentration, molecule 1 forms a gel at 10 mM concentration and a highly viscous sol at 5 mM concentration ( Fig. 2A, B).…”
Section: Resultsmentioning
confidence: 97%
“…Derivatives of the l-Phe-d-Oxd moiety may behave as fibre-like materials, [8] interact with lipid membranes, [9] form supramolecular helices [10] or be excellent organo-and hydrogelators, [11] also in the presence of metal ions. [13] In the continued search for new compounds that are able to gelate solvents, in this work we wished to analyse and compare the effect of substituent modification of the l-Phed-Oxd core and its replacement by the isosteric l-Phe-pGlu core (pGlu = pyroglutamic acid) and for this purpose we prepared a small library of 13 compounds. [13] In the continued search for new compounds that are able to gelate solvents, in this work we wished to analyse and compare the effect of substituent modification of the l-Phed-Oxd core and its replacement by the isosteric l-Phe-pGlu core (pGlu = pyroglutamic acid) and for this purpose we prepared a small library of 13 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…1), derived from natural proteinogenic amino acids (Thr, Phe) and a fatty acid (azelaic acid). Compound A was prepared from Boc-L-Phe-D-Oxd-OBn and azelaic acid, as previously reported [23]. To check the cellular uptake by confocal laser scanning microscopy, we prepared also three fluorescent compounds B , C and D , all containing the fluorescent dansyl group (Dans) [24].…”
Section: Resultsmentioning
confidence: 99%
“…CH 2 (C 3 H 6 CO-L-Phe-D-Oxd-L-Lys(Dansyl)OBn) 2 : As described in [23], a solution of Boc-L-Phe-D-Oxd-L-Lys(Dansyl)-OBn (0.24 mmol, 0.2 g) and TFA (4.32 mmol, 0.33 mL) in dry methylene chloride (10 mL) was stirred at room temperature for 4 h, then the volatiles were removed under reduced pressure and the corresponding amine salt was obtained pure in quantitative yield without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation